Impeccability and perfect virtue. Issue 2 (28th September 2016) - HENDERSON, LUKE
Abstract: Whatever else a theory of impeccability assumes about the moral life of heavenly agents, it seems to imply something about the type of actions possible for such agents, along with the quality of their moral characters. Regarding these characters, there are many that have argued impeccable and heavenly agents must also be perfectly virtuous agents. Michael Slote has recently argued, however, that perfect virtue is impossible. Assuming Slote's argument is successful, a theory of impeccability that relies on the possibility of perfect virtue would be greatly harmed, even to the point of incoherence. My intent here is to defend the coherence of the doctrine of impeccability, at least as it applies to the moral life of heavenly agents.